Produtos extrusados sem glúten obtidos de misturas de fécula de mandioca e farinha de arroz - Brunatti, Anna Claudia Sahade [UNESP] (2016)
Faced with the growing market for gluten-free products, the possibility of enhancement of cassava starch and rice flour asan ingredient for these products, and the importance of extrusion technology for the development of these; this study aimed to develop gluten-free products of rice and cassava through processing by extrusion. The cassava starch, rice flour and mixtures of these were analyzed for chemical composition, color, water solubility index, water absorption and pasting properties. After this analysis processing was performed by extrusion in single screw extruder. The extrusion process followed the central rotational design for four factors: percentage of cassava starch mixed with rice flour, moisture of mixtures, temperature in 3rd zone of the extrusion barrel and screw speed. The extruded expanded products obtained were analyzed for the expansion index, specific volume and hardness. It was performed grinding of the expanded product to obtain the pre-cooked flour and these were analyzed for color, water solubility index and water absorption index. The results were statistically analyzed and showed high starch content in cassava starch (81.79%) and protein (7.32%) in rice flour. The cassava starch showed higher water absorption index that rice flour, paste properties with low cold viscosity, high peak, high breakdown and high retrogradation tendency. The rice flour showed higher water solubility index and pasting properties with values below those observed for cassava starch. Thus, the mixture of two flours in different percentages led to changes in the physical characteristics of the mixtures. About the effects of extruding variable parameters on the physical properties of the extruded products it was observed that the percentage of cassava starch in the mixture had the greatest effect, followed by moisture. In expanded products are desirable high rates of expansion and specific volume and greater crispness, characteristics obtained under the conditions of low percentage of cassava starch in the mix, low moisture and lower screw speed, with intermediate extrusion temperature. However, for the production of pre-cooked flour are desired: clear color, high water absorption index and low water solubility index, which was observed under conditions of low percentage of cassava starch and moisture, with temperature and screw speed intermediates.